Language, Love, and Healing: A Psychoanalyst's Perspective - Gargiulo, Gerald J. ca. 20. Jh. (Journal of religion and health, 1999)
This lecture addresses the task of psychotherapy as enabling both patient and therapist to feel personally alive, sensibly responsible and to be able to experience compassion and civility. Freud's notion of the end of analysis issuing in a capacity for common unhappiness is examined. The metaphorical nature of psychotherapy is the frame for understanding these concepts.